(3NWHI GdfcGMs
(3ChdgG (B:s
(3CYhP HGddg ef GdTjWGf GdQLje HSe Gddg GdQMef GdQMje, GdMeO ddg LGYd GdXdeGJ hGdfhQ , heOjQ GdCRefg hGdOghQ s
(3BNQgG (B:s
(3gPG GdfcGM fcGMkG eHGQckG hOYGA eHGQckG hOYGmA eSJLGHI hebHhdI Ydi LeGYI GdMGVQjf hGdZGFHjf TQbkG hZQHkG HQkG hHMQkG HaVdc hcQec jG CcQe GdCcQejf hGdMeO ddg QH GdYGdejf Je s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
Keywords: (3Gdabg GdESdGejs